Experience-based decision support methodology for manufacturing technology selection: a fuzzy-decision-tree mining approach - Evans, Liam (2013)
Manufacturing companies must invest in new technologies and processes to succeed in a rapidly changing global environment. Managers have the difficulty of justifying capital investment in adopting new, state-of-the-art technology. Technology investment accounts for a large part of capital spending and is a key form of improving competitive advantage.